2011
DOI: 10.1042/bj20110112
|View full text |Cite
|
Sign up to set email alerts
|

Diverse mechanisms for activation of Wnt signalling in the ovarian tumour microenvironment

Abstract: Wnt signalling pathways have been shown to play key roles in both normal development and tumorigenesis. Progression of many human cancers is associated with defined mutations in Wnt pathway components that result in dysregulated β-catenin-mediated gene transcription. Although Wnt pathway mutations are rare in epithelial ovarian cancer (with the exception of the endometrioid histotype), accumulating evidence supports a role for Wnt signalling in ovarian tumorigenesis in the absence of genetic mutations. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 166 publications
(165 reference statements)
2
66
0
Order By: Relevance
“…In contrast to endometrioid ovarian carcinomas, which often harbor mutations in the ␤-catenin gene (23,24,52), activating mutations of Wnt signaling pathway components are rare in serous, clear cell, and mucinous ovarian carcinomas (53,54). Nevertheless, nuclear ␤-catenin has been observed in serous ovarian cancers, and coimmunoprecipitation of Lef-1 and ␤-catenin from serous tumors has been reported (53,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to endometrioid ovarian carcinomas, which often harbor mutations in the ␤-catenin gene (23,24,52), activating mutations of Wnt signaling pathway components are rare in serous, clear cell, and mucinous ovarian carcinomas (53,54). Nevertheless, nuclear ␤-catenin has been observed in serous ovarian cancers, and coimmunoprecipitation of Lef-1 and ␤-catenin from serous tumors has been reported (53,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Wnt5a, a ligand for the Frizzled receptor, is widely expressed in ovarian tumors and correlates with poor survival (73). Wnt5a is also prevalent in human ovarian cancer ascites fluid (52). There are conflicting data regarding the role of Wnt5a as an activator versus an inhibitor of canonical Wnt signaling (60, 74 -78), and additional studies are needed to clarify the role of this factor in ovarian cancer pathobiology.…”
Section: Discussionmentioning
confidence: 99%
“…9,21 Increased activity of the Wnt/β-catenin pathway can result from upregulation at different steps in the signaling pathway: overexpression of the cell surface receptors LRP5, LRP6, and Frizzled or increased activity of the Wnt target genes survivin, cyclin D1, Axin2, and c-myc. 9,13,22 A crucial component necessary for Wnt ligand transport, secretion, and activity is PORCN, which has been identified as a potential target to inhibit Wnt/β-catenin signaling. 15 Wnt pathway inhibitor success has been limited because of a narrow therapeutic window for activity since normal tissue stability requires Wnt/β-catenin signaling and a lack of predictive biomarkers of response.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that both GSK-3 and Axin2 are overexpressed in serous ovarian cancer. These findings implicate activation of Wnt/ -catenin signaling in serous EOC in the absence of activating mutations in either APC, Axin or -catenin (Barbolina et al, 2011).…”
Section: Ovarian Cancermentioning
confidence: 84%